Antidiarrheal Activity Test of a Combination of Guava Leaf Extract (Psidium guajava L.) and Kencur Rhizome (Kaempferia galanga) on Male Mice (Mus musculus) - Salmah Handayani Lubis; Muharni Saputri; Ika Julianti Tambunan; Adilla Apriliani; Della Aisyah Syah Fitri (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background Diarrhea is the leading cause of high morbidity and mortality in children in developing countries such as Indonesia. Diarrhea can be caused by bacterial infections. Guava leaves and kencur have astringent properties that can help reduce the frequency of bowel movements and stop diarrhea. Aim: The study aims to determine the most effective dose concentration of a combination of guava leaf ethanol extract (PGEE) and kencur rhizome ethanol extract (KGEE) as an antidiarrheal medicine. Methods: The study used an experimental method with stages of simplisia preparation, extract preparation by maceration, simplisia characteristics, phytochemical screening, and antidiarrheal efficacy testing using 25 male mice divided into 5 groups, namely F1 = negative control (NaCMC); F2 = positive control (Loperamide); F3, F4, and F5 were combinations (PGEE:KGEE) with 3 different dose concentrations, namely (25%:75%); (50%:50%), and (75%:25%), where the base doses used were (PGEE=400mg/kg/BW) and (KGEE=27.5mg/kgBW). Results: The parameters observed included the onset time of diarrhea, duration, frequency of bowel movements, and stool consistency. Statistical data analysis was performed using ANOVA and Tukey's post hoc test with the help of SPSS software. Statistical analysis with Tukey's post hoc test showed that there was a significant difference (p < 0.05) in fecal weight between the treatment group and the negative control group. Conclusion: The dose concentration (50%:50%) showed the most significant effect in reducing fecal weight comparable to loperamide, so that the combination of PGEE and KGEE at that dose concentration proved to be the most effective in reducing fecal weight and overcoming diarrhea, both visually (graph) and based on statistical analysis results.